Efektivitas Dakwah melalui Pemanfaatan Budaya Madihin sebagai Alat Komunikasi Masyarakat Kalimantan Selatan - Muhammad Noor Ridani; Dian May Syifa; Rena Zulfaidah (IAIN Batusangkar, 2023)
South Kalimantan is an area that has various cultures, one of the cultures owned is the art of madihin, this culture is packaged with chanting poetry and instruments from tarbang. But not just performing arts, madihin culture also has many values contained in it. This paper uses a literature study research method, with a descriptive qualitative approach, by studying, examining in depth and then linking it to the formulation of the problem, namely how the role of madihin culture as a communication tool in South Kalimantan and how the integration of Islamic values and madihin local culture as the effectiveness of da'wah. The results showed that madihin culture has a dual function apart from being a performing art but also as a means of communication for the people of South Kalimantan which is packaged in a way that easily attracts the attention of the audience in conveying the message to be conveyed through its verses, madihin is evidence of the integration of Islam with local culture to be useful as the effectiveness of da'wah, as well as proof that Islam is universal because it does not question culture as long as it does not conflict with the sharia, the utilization of madihin culture as a communication tool in da'wah is useful as a da'wah strategy in delivering the chanting of the sharia as well as being a place to preserve the local culture of South Kalimantan which will not sink in the development of the times in the future.